Aberrant myocardial calcium cycling: pathogenic mechanisms and targeted therapeutics for heart failure - Chunxiao Zhao; Jiahao Liu; Juanjuan Xin; Qun Liu; Ying Zhang; Xiaochun Yu; Junhong Gao (Frontiers in Cardiovascular Medicine, 2026)
Cardiovascular diseases rank as the global primary cause of mortality. Heart failure (HF) represents a progressive cardiac syndrome triggered by structural or functional myocardial damage that compromises ventricular systolic output. Intracellular calcium homeostasis underpins cardiomyocyte excitation-contraction coupling. Calcium overload and dysregulated calcium handling act as central pathogenic forces driving HF progression. Sympathetic β 1 -adrenergic receptor (β 1 -AR) and parasympathetic M 2 muscarinic acetylcholine receptor (M 2 -AChR) coordinate dual regulatory signaling to control cardiac calcium turnover, alongside key modulators including L-type calcium channel (LTCC), ryanodine receptor 2 (RyR2), SERCA2a, cardiac troponin C (cTnC), Na + /Ca 2+ exchanger 1 (NCX1) and mitochondrial permeability transition pore (MPTP). This review outlines physiological calcium cycling and systematically characterizes HF-related functional defects of calcium regulatory machinery from three layers: calcium release, sarcoplasmic reticulum calcium reuptake and auxiliary calcium mediators. We further discuss the underlying mechanisms of calcium-targeted pharmaceuticals and gene therapeutic approaches, while addressing translational bottlenecks limiting single-target interventions. Restoration of balanced cytosolic calcium cycling holds therapeutic potential to reverse pathological myocardial remodeling in HF.